ДИДАКТИЧЕСКИЕ ВОЗМОЖНОСТИ ЭСТЕТИЧЕСКОГО ВОСПИТАНИЯ УЧЕНИКОВ НАЧАЛЬНЫХ КЛАССОВ С ПОМОЩЬЮ НАЦИОНАЛЬНЫХ ПОДВИЖНЫХ ИГР - Зайниддинов, Т.Б. (SCIENCE and SOCIETY, 2019)
The article deals with the didactic potential of aesthetic education of pupils through national mobility games, in which the ideas on the use of didactic requirements and techniques for aesthetic education of pupils are presented.